Makna Penataan Interior Rumah Tradisional Jawa - Budiwiyanto, Joko (Pendhapa, 2009)
This article is a part of the result of the research on the function and meaning of interior design of dalem pangeran. This research aims at finding out the meaning contained in the interior design of Javanese houses. The result of the research shows that in case of the interior design, dalem pangeranis always oriented towards symbolic classification based on two, four, and eight. The outlook on classification two often manifested in kiwo-tengen(left-right), atas-bawah (top-down), or loroning atunggal (two in one) is always integrated into something greater and absolute. This view is not a contrast but a relation of two different things which is harmonious. The symmetric concept in designing interior elements shows the existence of the symbolic and harmonious meanings. The concept is the manifestation of balance aiming at attaining the harmony of life, that is, to live harmoniously with each other, with nature, and with God. Key words : Javanese house, interior, meaning